Detection and characterization of tree shrew retinal venous pulsations: An animal model to study human retinal venous pulsations. (August 2019) - Dattilo, Michael; Read, A. Thomas; Samuels, Brian C.; Ethier, C. Ross
Abstract: Spontaneous retinal venous pulsations (SRVPs), pulsations of branches of the central retinal vein, are affected by intraocular pressure (IOP) and intracranial pressure (ICP) and thus convey potentially-useful information about ICP. However, the exact relationship between SRVPs, IOP, and ICP is unknown. It is not easily feasible to study this relationship in humans, necessitating the use of an animal model. We here propose tree shrews as a suitable animal model to study the complex relationship between SRVPs, IOP, and ICP. Tree shrew SRVP incidence was determined in a population of animals. Following validation of a modified IOP control system to accurately and quickly control IOP, IOP and/or ICP were manipulated in two tree shrews with SRVPs and the effects on SRVP properties were quantified. SRVPs were present in 75% of tree shrews at physiologic IOP and ICP. Altering IOP or ICP produced changes in tree shrew SRVP properties; specifically, increasing IOP caused SRVP amplitude to increase, while increasing ICP caused SRVP amplitude to decrease. In addition, a higher IOP was necessary to generate SRVPs at a higher ICP than at a lower ICP. SRVPs occur with a similar incidence in tree shrews as in humans, and tree shrew SRVPs are affected by changes in IOP and ICP in a manner qualitatively similar to that reported in humans. In view of anatomic similarities, tree shrews are a promising animal model system to further study the complex relationship between SRVPs, IOP, and ICP. Highlights: Tree shrews have retinal venous pulsations at physiologic IOP and ICP. Tree shrew retinal venous pulsation incidence is similar to humans. Tree shrew and human retinal venous pulsations are affected similarly by IOP & ICP. Tree shrews may be an appropriate animal model to study retinal venous pulsations.